Prevalence of Smartphone Addiction and its Relationship with Obesity among Young Adults: A Cross-sectional Study from Delhi, India - Priyosmita Das; Kallur Nava Saraswathy; Vineet Chaudhary (Wolters Kluwer Medknow Publications, 2024)
Smartphone addiction (SA) has emerged as an important health concern worldwide. Recent studies have recognized SA as one of the factors that promote sedentarism and can contribute to obesity. However, the relationship between SA and obesity among Indian young adults remains understudied. The present study aims to estimate the prevalence of SA and explore its association with general and central obesity among young adults in Delhi, India. This cross-sectional study was conducted among 246 young adults (aged 18-30 years) of either sex (60.16% females) from Delhi. Screening for SA was done using the Smartphone Addiction Scale-Short Version. Somatometric measurements (height, weight, waist circumference, and hip circumference) were taken to determine general and central obesity. SA was prevalent among 25.2% of the participants. The prevalence of SA was higher among males and undergraduate students than among females and postgraduate/MPhil/PhD students, respectively. Further, SA was not associated with any of the obesity variables. Interestingly, smartphone addicts were found to have a 2.5-fold increased risk of being underweight. Though SA was not associated with obesity, it was found to be associated with being underweight, indicating a relationship between smartphone use and nutritional status among young adults.